1989
DOI: 10.1016/0014-5793(89)80255-8
|View full text |Cite
|
Sign up to set email alerts
|

Chicken red‐sensitive cone visual pigment retains a binding domain for transducin

Abstract: Iodopsin (a red-sensitive cone visual pigment) and rhodopsin (a rod pigment) were isolated from chicken retina. They were separately reconstituted into phosphatidylcholine liposomes and then mixed with rod transducin (Tot and TB~') purified from bovine retina, lodopsin enhanced, only when irradiated, the binding of GppNHp to T~t to a similar extent to irradiated rhodopsin. Furthermore, the binding of GppNHp to T~ in the presence of a photobleaching intermediate of iodopsin preferably required Tfly-2 rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
11
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 12 publications
6
11
1
Order By: Relevance
“…cG and mG at 0 -37°C. It should be noted that this finding is inconsistent with previous reports showing that the initial velocity of G t activation by cone visual pigments was similar to that of rhodopsin (7,9,10). The previous studies were performed in the presence of about a 10-fold excess of G t using the pigments in liposomes or native membranes at 0 or 4°C.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…cG and mG at 0 -37°C. It should be noted that this finding is inconsistent with previous reports showing that the initial velocity of G t activation by cone visual pigments was similar to that of rhodopsin (7,9,10). The previous studies were performed in the presence of about a 10-fold excess of G t using the pigments in liposomes or native membranes at 0 or 4°C.…”
Section: Discussioncontrasting
confidence: 93%
“…It has been reported previously that the G t activation efficiencies of rhodopsin and cone visual pigments were similar to each other based on experiments performed at about 0°C (7,9,10), although those of rhodopsin and cone visual pigments of a poikilothermic animal (carp) were recently reported to be different at 20°C (11,12). Thus, it is likely that the difference in amplification efficiency between wild-type rods and rods con-taining mG is caused by temperature-dependent intrinsic properties of visual pigments such as the thermal equilibrium between active state Meta-II and its precursor Meta-I and/or the lifetime of Meta-II that may compete with the deactivation process consisting of phosphorylation by rhodopsin kinase (7).…”
supporting
confidence: 74%
“…Nevertheless, rods and cones exhibit distinctive light responses: Rods have several hundred times higher sensitivity to light than cones, whereas cones recover from photoexcitation much faster than rods (Baylor 1996), and the molecular mechanism(s) underlying these differences largely remains to be elucidated. The activation kinetics of transducin by cone pigments was similar to that by rhodopsin (Fukada et al . 1989; Starace and Knox 1997), and the photoresponse recorded from the transgenic Xenopus rods expressing cone pigment was indistinguishable from that of the wild‐type rods (Kefalov et al .…”
mentioning
confidence: 73%
“…Previously, several studies on the chicken red cone pigment have demonstrated that it activates transducin (4,25,27) and the cGMP phosphodiesterase (28) and is a substrate for rhodopsin kinase (29). Although these studies have demonstrated the basic interactions, kinetic comparisons relevant to cone-rod physiological differences were not carried out.…”
Section: Discussionmentioning
confidence: 99%